Comparison of Free Flap Outcomes at a University Hospital versus County Hospital Setting for Head and Neck Reconstruction - Swanson, Mark S.; Gantz, Oliver; Zhou, Sheng; Fisher, Laurel; Kezirian, Eric; Tan, Michael H.; Zhang, Yanchen; Chambers, Tamara N.; Sinha, Uttam K.; Kokot, Niels (International Archives of Otorhinolaryngology, 2023)
Introduction Patients at public county hospitals often have poorer access to healthcare with advanced disease on presentation. These factors, along with limited resources at county hospitals, may have an impact on outcomes for patients requiring complex head and neck reconstruction.Objective To delineate differences in the frequency of complications in two different care settings, a public county hospital and a private university hospital.Methods Retrospective review of otolaryngology patients at a university hospital compared with a publicly-funded county hospital. The main outcome measure was major complications including total flap loss or unplanned reoperation in 30 days. Secondary outcome measures included medical complications, partial flap loss, and unplanned hospital readmission in 30 days.Results In the county hospital sample (n = 58) free flap failure or reoperation occurred in 20.7% of the patients, and minor complications, in 36.2% of the patients. In the university hospital sample (n = 65) flap failure or reoperation occurred in 9.2% of the patients, and minor complications, in 12.3% of the patients. Patients at the private hospital who had surgery in the oropharynx were least likely to have minor complications.Conclusion Patients at the county hospital had a higher but not statistically significant difference in flap failure and reoperation than those at a university hospital, although the county hospital experienced more minor postoperative complications. This is likely multifactorial, and may be related to poorer access to primary care preoperatively, malnutrition, poorly controlled or undiagnosed medical comorbidities, and differences in hospital resources.
Keywords: free tissue flaps; head and neck cancer; reconstructive surgery; public hospitals; postoperative complications